Social media capability in B2B marketing: toward a definition and a research model. Issue 8 (2nd October 2017) - Wang, Yun; Rod, Michel; Ji, Shaobo; Deng, Qi
Abstract : Purpose: The purpose of this study is to explore organizational social media capability in business-to-business (B2B) marketing, by focusing on what social media capability is in a B2B marketing context and how it is developed in firms engaged in B2B marketing. Design/methodology/approach: This is a thematic literature review, drawing on both B2B marketing and Information Systems literature. In total, 112 academic articles from nine journals were identified and analyzed. The findings were synthesized and compiled to provide answers to the predefined research questions. Findings: The results suggest that organizational social media capability is dependent on a deep understanding of a firm's technological capability, i.e. recognizing the key features and categories of social media and dynamically upgrading the recognition in response to the environmental change. A four-level Social Media Capability Maturity Model (technological, operational, managed and strategic level) that collectively transfers social media's technological capability to dynamic organizational capability is proposed. Originality/value: This study contributes to an understanding of the use of social media in the context of B2B marketing from an organizational dynamic capability perspective. The model is particularly relevant to organizations that have adopted or plan to adopt a B2B social media strategy and is relevant for B2B researchers who are interested in social media research.